Illustrated identification key to females of the genus Sabethes Robineau-Desvoidy recorded from Brazil (Diptera: Culicidae), in dichotomous and interactive formats, including an updated list of species and new records for the states - Neves, Maycon Sebastião Alberto Santos; Motta, Monique Albuquerque; Maciel-De-Freitas, Rafael; Xavier, Alexandre Da Silva; Lourenço-De-Oliveira, Ricardo; Silva-Do-Nascimento, Teresa Fernandes (Zootaxa, 2024)
Female mosquitoes of the genus Sabethes Robineau-Desvoidy, 1827 are implicated in the transmission of several arboviruses, including yellow fever virus. Here, we present an illustrated species identification key for females of the genus Sabethes recorded in Brazil, except Sa. nitidus Theobald, 1901 and Sa. harbachi Nascimento-Pereira, Guimarães, Lourenço-de-Oliveira & Motta, 2021 as only the males of these species are known. The key is available in dichotomous and interactive formats. An updated list of the Sabethes species of Brazil and new occurrence records for the states of the country are provided. The type localities of four species—Sa. glaucodaemon (Dyar & Shannon, 1925), Sa. amazonicus Gordon & Evans, 1922, Sa. belisarioi Neiva, 1908 and Sa. soperi Lane & Cerqueira, 1942—are corrected or restricted.